Democratic Republic of Sao Tome and Principe : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The statistical data on gross domestic product and expenditure, land distribution, production of principal agricultural crops, energy production and consumption, imports of petroleum products, cost structure of petroleum products, consumer price index, and financial transactions of the central government of the Democratic Republic of Sao Tome have been presented. The summary accounts of banking institutions, structure of interest rates, composition of exports, import, and terms-of-trade indices, indicators of external public debt, exchange rates, and related economic indices have also been presented.